2013
DOI: 10.4236/health.2013.55a005
|View full text |Cite
|
Sign up to set email alerts
|

ATP binding cassette C1 (ABCC1/MRP1)-mediated drug efflux contributes to disease progression in T-lineage acute lymphoblastic leukemia

Abstract: Purpose In acute lymphoblastic leukemia (ALL), multidrug resistance is often mediated by ATPase Binding Cassette (ABC) proteins, which principally involve ABCB1 (multidrug resistance 1, MDR1) and ABCC1 (multidrug resistance protein 1, MRP1). However, direct comparisons between the differential effects of ABCB1 and ABCC1 have been difficult, since identical cell lines with differential expression of these transporters have not been developed. Experimental Design In this study, we developed and compared the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Our analyses revealed that the ADME variant with the strongest evidence for an association with VIPN, rs3784867 ( P = 5.34 × 10 −5 ; OR = 4.91; 95% CI = 1.99–12.10), occurs in the intron of ABCC1 . This gene encodes multidrug resistance protein 1, a protein, which is involved in both transport of, and resistance to, vincristine . ABCC1 has also been implicated in anthracycline‐related and methotrexate‐related pharmacogenomic phenotypes .…”
Section: Discussionmentioning
confidence: 99%
“…Our analyses revealed that the ADME variant with the strongest evidence for an association with VIPN, rs3784867 ( P = 5.34 × 10 −5 ; OR = 4.91; 95% CI = 1.99–12.10), occurs in the intron of ABCC1 . This gene encodes multidrug resistance protein 1, a protein, which is involved in both transport of, and resistance to, vincristine . ABCC1 has also been implicated in anthracycline‐related and methotrexate‐related pharmacogenomic phenotypes .…”
Section: Discussionmentioning
confidence: 99%
“…For the above reasons, it is difficult to find a feasible transmembrane transport protein reversal agent in clinical practice. At present, many researchers have focused on new chemical sensitizers or new methods to specifically down-regulate the expression of multidrug resistance genes, such as small molecule inhibitors, natural drugs, RNA interference, epigenetic regulation, or signal transduction pathways [27,33,34,35,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, ABCC1 also plays a role in the chemoresistance of different cancers. For instance, high ABCC1 expression is a negative prognostic factor in cases of soft tissue sarcoma (Citti et al, 2012;Martin-Broto et al, 2014) and acute myeloid and lymphoblastic leukemia (van der Kolk et al, 2000;Winter et al, 2013;Liu et al, 2018). Furthermore, this correlation has been shown for neuroblastoma patients.…”
Section: Introductionmentioning
confidence: 96%